A Prospective Study of HIV Positive Autopsies Conducted at Aniims, Port Blair, Andaman & Nicobar Islands - Siddesh Revpla Channabasappa; Amit Banik (Indian Journal of Forensic Medicine & Toxicology, 2021)
Medical and Medico Legal deaths claim a substantial number of lives in Andaman & Nicobar Islands. Duringthe 3-year-period from January 2016 to December 2018, 6 antibody HIV positive cases were autopsied at theDepartment of Forensic Medicine & Toxicology in ANIIMS, Port Blair, Andaman and Nicobar Islands. Thepurposes of this study were to report the autopsy findings of anti-HIV positive individuals, and to identifythe prevalence of specific factors such as gender, age, postmortem findings, cause and manner of death.The 61 anti-HIV positive individuals who died at G B Pant Hospital, Port Blair consisted of 35 males and26 females. Here, 55 cases died from natural cause, 6 cases due to unnatural causes termed as medico legaldeath, which included 2 cases of accidents and 4 cases of suicide. All Medico legal cases underwent fullautopsy with universal precautions.The prevalence of anti-HIV positive underlined the importance of awareness of HIV transmission in forensiccasework. In conclusion, full autopsies should be performed regularly on HIV infected patients with dueprotective measures not only for medical research, but also for forensic study